Avaliação de um programa de ensino para cuidadores desenvolverem a linguagem oral das crianças de forma naturalística - Balog, Lívia Gabriela Campos (Universidade Federal de São Carlos, 2024)
This thesis presents three studies that supported the planning, implementation and evaluation of an intervention for caregivers to apply naturalistic strategies to expand children's communication repertoire. Firstly, a systematic review of the literature was carried out with the aim of analyzing methods of teaching parents to develop the language of their children with intellectual disabilities, delays or language impairment, within the family routine. The strategies taught to parents most used by studies were described, as follows: a) follow the child's interest, b) be responsive, c) organize the environment, d) expand the child's communication, e) ask questions d) provide breaks . Discuss the different ways of teaching naturalistic language stimulation strategies to parents, including the increasing use of technologies for teaching and monitoring caregivers. Based on the literature review carried out in Study 2, the objective is to develop and evaluate a remote parenting program to stimulate children's language in the family routine, in the context of social isolation. Although the remote teaching model was well evaluated by caregivers and the study achieved its initial objectives, some limitations were highlighted. Considering the limitations of Study 2, Study 3 was designed and aimed to verify the effect of the program, carried out in person, with phases of instruction, modeling and feedback on parents' behaviors. The results of both studies demonstrated the effectiveness of the intervention in increasing the frequency of use of strategies by parents and in some measures of children's language. Suggestions were proposed for conducting future studies and we hope that the results can help in the development of naturalistic disciplines aimed at caregivers, especially children with ASD, Down Syndrome and delays in language development.
Evaluation of a teaching program for caregivers to develop children's language in a naturalistic context
Keywords: Ensino naturalístico; Linguagem; Treinamento de cuidadores; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::PROGRAMACAO DE CONDICOES DE ENSINO